Received Signal Level (RSL) Strength Assessment of 2.4 GHz in A Hotel Meeting Room - Fauzi, Amar; Arrofiq, Muhammad (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2020)
This study aims to analyze the signal quality of the building profile factor at the Ballroom of Tentrem Hotel Yogyakarta, organized by the value of RSL (Received Signal Level) as an indicator of signal strength level of each access point of the Tentrem Hotel Ballroom meeting room, and calculate other parameters such as EIRP (Effective Isotropic Radiated Power), free space loss with theoretical and measurement levels. Receive level signals in the field using the Netsurveyor and Vistumbler applications installed on the laptop and the Wifi Overview and Wifi Analyzer app installed on the smartphone. From the results of both RSL calculations in theory and its changes. Damping factors in the field such as diffraction effect, refraction, reflection, absorption or blocking. The average field summary shows the RSL values in turn